Surface relief phenomenon in NiTi shape memory alloys - Zhang, Wenhua (2008)
Surface relief is one of the interesting properties of shape memory alloys (SMAs). Heating and cooling can change the surface roughness and reflection coefficients of SMAs. In present project, this phenomenon in NiTi rods was investigated quantitatively; it should be the first one to the best knowledge of this author. The potential applications are in micro optical devices. The aim of this dissertation was to investigate the variation of the surface relief of NiTi SMA against temperature. It may provide a very useful guide on the design of SMA based micro optical devices.